Kajian Gangguan Harmonisa dan Simulasi Perbaikan Sistem Kelistrikan Di Gedung Rektorat Politeknik Negeri Ketapang - Ivan Suwanda (Energi & Kelistrikan, 2019)
This research can be used to determine the quality and improvement of the electrical system in the Ketapang State Polytechnic rectorate building. Electrical interference can cause electrical equipment not working to the maximum which can cause permanent damage to the electrical equipment itself. The disturbance can be in the form of harmonic waves. Both of these electrical problems are very difficult for me to improve the quality of electric power. This research uses ETAP 16.00. Improvement efforts in the simulation is to use several filters that will be selected as the best filter that can reduce harmonic waves. Before using the filter the total harmonic distortion (THD) value reached 7.1% THD. After answering with several types of filters namely a single filter set, by-pass, and high-pass (not named) that can reduce harmonics to the maximum is a single filter set with a value of 2.63% THD which means the value is still in the range of THD value added which is a maximum of 5% THD.